Elevated CO2 Increases Nitrogen Fixation at the Reproductive Phase Contributing to Various Yield Responses of Soybean Cultivars - Li, Yansheng; Yu, Zhenhua; Liu, Xiaobing; Mathesius, Ulrike; Wang, Guanghua; Tang, Caixian; Wu, Junjiang; Liu, Judong; Zhang, Shaoqing; Jin, Jian (Frontiers in Plant Science, 2017)
Nitrogen deficiency limits crop performance under elevated CO2 (eCO2), depending on the ability of plant N uptake. However, the dynamics and redistribution of N2 fixation, and fertilizer and soil N use in legumes under eCO2 have been little studied. Such an investigation is essential to improve the adaptability of legumes to climate change. We took advantage of genotype-specific responses of soybean to increased CO2 to test which N-uptake phenotypes are most strongly related to enhanced yield. Eight soybean cultivars were grown in open-top chambers with either 390 ppm (aCO2) or 550 ppm CO2 (eCO2). The plants were supplied with 100 mg N kg−1 soil as 15N-labeled calcium nitrate, and harvested at the initial seed-filling (R5) and full-mature (R8) stages. Increased yield in response to eCO2 correlated highly (r = 0.95) with an increase in symbiotically fixed N during the R5 to R8 stage. In contrast, eCO2 only led to small increases in the uptake of fertilizer-derived and soil-derived N during R5 to R8, and these increases did not correlate with enhanced yield. Elevated CO2 also decreased the proportion of seed N redistributed from shoot to seeds, and this decrease strongly correlated with increased yield. Moreover, the total N uptake was associated with increases in fixed-N per nodule in response to eCO2, but not with changes in nodule biomass, nodule density, or root length.